TINJAUAN TENTANG PEMBERIAN SANTUNAN DANA KECELAKAAN LALU LINTAS JALAN TERHADAP KORBAN OLEH PT. ASURANSI JASA RAHARJA DI KOTA PALU - Mursyid, Besse Tenriabeng (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2020)
The developments of science and technology particularly in traffic and transportation field, apparently not only have benefits and positive effects on people’s life behavior, but also create negative impacts, traffic accidents, for instance. Victims of traffic accidents both minor and serious injuries as well as the heirs of the dead victims do need funds for medical expenses and funeral costs. Therefore, whoever has traffic accident, in fact, is entitled to compensation from Jasa Raharja. Jasa Raharja claim process begins by filling out the form as good and honest as possible based on valid documents. This process takes at least one to two hours, or a whole day, it depends on the number of people who submit claims at the same time.